Addressing sufficiency: Including altruistic motives in behavioural models for sustainability transitions - Niko Schäpke; Felix Rauschmayer (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
The main motivation for sustainable development, as defined in the Brundtland report, is to care for other humans - for the world's poor and for unborn people. Traditional economic models use the motivation to increase one's own well-being as the main motivation for action. Efficiency-improvements, as the main focus of the economics-based models have largely shown to be ineffective, due to rebound effects etc. We assume that efficiency or consistency improvements can only be effective when accompanied by a more fundamental value shift. A shift including altruistic motivations for behaviour, as they are part of sufficiency strategies for sustainable development. Models that reduce motivations for actions to self-centred ones cannot account for such change. The Capability Approach as an alternative to neo-classical approaches, distinguishes between interests in own well-being and other-regarding interests. Yet it has seldom been applied to address the latter. Tested psychological models that encompass both motivations, on the other hand, have no scope for analysing wider societal effects of policies. This paper therefore integrates psychological knowledge in a capability framework, to be used as a basis for empirical analyses. The developed model should allow the design and assessment of efficiency, consistency, and sufficiency strategies for sustainability transitions.
Keywords: 330